(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
In the past decades English language teaching (and generally we might say foreign language teaching) has changed a lot. Communicative language teaching has become the most popular and widely recognized form of teaching and learning. This approach emphasises interaction as both the means and the ultimate goal of learning a language. In Central-Eastern Europe foreign language teacher training hardly deals with communicative approach, it is mostly about old theories and a little practice. Those who wish to learn how to teach in a communicative way enrol a CELTA Teacher Training (Certificate in Teaching English to Speakers of Other Languages issued by University of Cambridge ESOL) organized worldwide. Recently I have taken part in a CELTA Teacher Training course. One of the course requirements was writing an essay on a self-designed teaching material for our practice teaching groups (my students’ level was upper-intermediate).